GEOGRAPHIA TECHNICA NR. 2/2012 - HAIDU, Ionel (Presa Universitară Clujeană, 2012)
Geographia Technica is a journal devoted to the publication of all papers on all aspects of the use of technical and quantitative. It aims at presenting its readers with the latest developments in G.I.S technology, mathematical methods applicable to any field of geography, territorial micro-scalar and laboratory experiments, and the latest developments induced by the measurement techniques to the geographical research. Geographia Technica is dedicated to all of those who understand the nowadays every field of geography can only be described by specific numerical values, variables both oftime and space which require the sort of numerical analyses only possible with the aid of technical and quantitative methods offered by powerful computers and dedicated software. The publication intends to serve workers in academia, industry and government. Students, teachers, researchers and practitioners should benefit from the ideas in the journal.